Cork processing wastewaters components fractioned by ultrafiltration membranes – studies of antioxidant and antitumoral activity. Issue 3 (1st November 2017) - Gomes, Luís; Borges, Carlos; Serralheiro, M Luísa M; Minhalma, Miguel; Pacheco, Rita
Abstract: BACKGROUND: Cork processing wastewater is an environmental problem due to its high content of organic matter, such as sugars and non‐biodegradable compounds such as polyphenols (PPs), namely tannins. Membrane technology aimed at valorisation of the wastewaters components, concentrate stream, and simultaneously offer a pre‐treatment of the wastewater, permeate stream. In this work, the identification of bioactive PPs was also envisaged. Several fractions of cork processing wastewaters were generated using two cellulose acetate ultrafiltration membranes of 3 kDa and 74 kDa for PPs isolation according to nature and molecular weights. The membranes were prepared by the phase inversion method and fractionation was made in concentration and diafiltration modes. The wastewater and the fractions were analyzed in terms of total organic carbon, total phenols, tannins and total polysaccharides content and the compounds present were identified by FTIR, LC–MS and quantified by HPLC‐DAD. RESULTS: Compounds such as quinic, gallic, protocatechuic, brevifolin carboxylic and ellagic acids were identified as the major compounds in cork wastewater. The wastewater and the fractions were tested for antioxidant activity and for capacity to inhibit the proliferation of the growth of human breast carcinoma cell lines, MCF‐7. The fractions revealed high antioxidant activity with EC50 values ranging from 1.174 ± 0.069 to 1.943 ± 0.179 mg/mgDPPH . The fractions demonstrated to be efficient as cell proliferation inhibitors, with values of IC50 ranging from 0.20 ± 0.003 to 0.46 ± 0.02 mg mL ‐1 . CONCLUSION: The process reported demonstrates that PPs compounds can be recovered from cork effluent and further reused as high‐value bioactive compounds. © 2017 Society of Chemical Industry